Implementation of social media marketing in increasing brand awareness on instagram accounts @Feraastriamakeup - Agnes Veren Nica; Annisa Wahyuni Arsyad; Silviana Purwanti (Institute of Computer Science (IOCS), 2023)
Social media has now become a trend in the world of marketing communications. The purpose of this study is to determine the implementation of social media marketing in increasing brand awareness on Instagram accounts. The type of research chosen by the researcher is a type of qualitative research. Qualitative research is research. In increasing Brand Awareness on the Instagram account @feraastriamakeup influenced by several variables, namely Customer Engagement, Viral Marketing, Buzz Marketing, Peer Influence, and Online Communities. From the results of the interview, it can be concluded that the content review from the Customer is considered good where the content presented by @feraastriamakeup is very interesting and keeps up with the times. Whereas in terms of reservations, Customer @feraastriamakeup prefers to use Social media Instagram and Whatsapp. The use of social media Instagram on @feraastriamakeup and consumer responses to the formation of Brand Awareness at @feraastriamakeup has a very big influence where customer perceptions are not only on the price of make-up services but on the quality of make-up.